The Blood Pressure Lowering Treatment Trialists’ Collaboration: methodological clarifications of recent reports - Nazarzadeh, M; Canoy, D; Bidel, Z; Copland, E; Rahimi, K; Teo, K; Davis, BR; Chalmers, J; Pepine, CJ; Woodward, M (Lippincott, Williams & Wilkins, 2022)
Epidemiological evidence has consistently shown that people with higher systolic or diastolic blood pressure are at greater risk of cardiovascular diseases. However, there has been limited randomized evidence to determine the role of blood pressure level at treatment initiation in the reduction of cardiovascular diseases risk. The extent to which other characteristics of individuals, such as prior disease history, age or sex, should be taken into account has also been controversial. Furthermore, effects on less commonly reported efficacy and safety outcomes remain underexplored. The Blood Pressure Lowering Treatment Trialists' Collaboration has collected individual-level participant data from 52 randomized clinical trials, with more than 360 000 participants, and is now the largest source of individual-level data from randomized clinical trials of blood pressure-lowering treatment. This resource provides an unprecedented opportunity to address major areas of uncertainty relating to stratified efficacy and safety of antihypertensive therapy. Recent reports have demonstrated the power of pooled analyses of the Blood Pressure Lowering Treatment Trialists' Collaboration dataset in filling long-standing gaps in our knowledge. However, there have been some misconceptions regarding the methods underpinning the recent reports, which we clarify in this article.